Letter - Ferguson, T. M.
038-0037-001 Telephone No. 5273 Dundee and District Union of Jute and Flax Workers Affiliated with the General Federation of Trade Unions and the British and Scottish Trades Union Congresses T.M. FERGUSON Secretary In reply please quote Ref. 422/40. 69/71 NETHERGATE, DUNDEE 30th December 1940. The Secretary, British Trades Union Congress, Transport House, Smith Square, LONDON. S.W.1 Dear Sir, A Circular letter dated 11th December 1940 has been sent us by the "National Joint Committee for Spanish Relief" asking for financial assistance for the keeping of 400 Basque Children and 300 adult refugees. I am instructed by my Executive Committee to enquire if Congress is doing anything in this matter, at present, or if the Fund that was in existence is now closed. An early reply will oblige. Yours faithfully. T M Ferguson Secretary. 292/946/38/37